Ответ:
[tex]а)6(n - 2m)[/tex]
[tex]б)- 4( \frac{1}{5} p + t)[/tex]
Пошаговое объяснение:
[tex]а)6n - 12m = 6(n - 2m)[/tex]
[tex] б)- 0.8p - 4t = - \frac{4}{5} p - 4t = - ( \frac{4}{5} p + 4t) = - 4( \frac{1}{5} p + t)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]а)6(n - 2m)[/tex]
[tex]б)- 4( \frac{1}{5} p + t)[/tex]
Пошаговое объяснение:
[tex]а)6n - 12m = 6(n - 2m)[/tex]
[tex] б)- 0.8p - 4t = - \frac{4}{5} p - 4t = - ( \frac{4}{5} p + 4t) = - 4( \frac{1}{5} p + t)[/tex]